2012
DOI: 10.1073/pnas.1208228109
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing crystal-like amyloid fibrils and glass-like amorphous aggregates from their kinetics of formation

Abstract: Amyloid fibrils and amorphous aggregates are two types of aberrant aggregates associated with protein misfolding diseases. Although they differ in morphology, the two forms are often treated indiscriminately. β 2 -microglobulin (β2m), a protein responsible for dialysis-related amyloidosis, forms amyloid fibrils or amorphous aggregates depending on the NaCl concentration at pH 2.5. We compared the kinetics of their formation, which was monitored by measuring thioflavin T fluorescence, light scattering, and 8-an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

21
369
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 278 publications
(391 citation statements)
references
References 47 publications
21
369
1
Order By: Relevance
“…10(a)]. 51) Yoshimura et al 51) also proposed a general phase diagram for various conformational states of peptides and proteins determined by conformational uniqueness [ Fig. 10(b)].…”
Section: Distinguishing Crystalline Fibrils and Glassy Amorphous Aggrmentioning
confidence: 99%
See 2 more Smart Citations
“…10(a)]. 51) Yoshimura et al 51) also proposed a general phase diagram for various conformational states of peptides and proteins determined by conformational uniqueness [ Fig. 10(b)].…”
Section: Distinguishing Crystalline Fibrils and Glassy Amorphous Aggrmentioning
confidence: 99%
“…Yoshimura et al 51) monitored the effects of ultrasonication on fibrillation of 2-m in real time. The sample solution in a cuvette was irradiated with ultrasonication pulses by tightly attaching an ultrasonic generator to the sidewall of the cuvette as shown in Fig.…”
Section: Distinguishing Crystalline Fibrils and Glassy Amorphous Aggrmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of supersaturation has recently been reported in the context of widespread aggregation and neurodegenerative diseases (24). Although the physicochemical mechanism of supersaturation remains unclear, we have suggested that ultrasonication is one of the most powerful agitations breaking the otherwise persistent metastability of supersaturation (19,23,(25)(26)(27).…”
mentioning
confidence: 99%
“…Under labile conditions in which the driving forces of precipitation increase, spontaneous crystallization can occur after a certain period of lag time. Further increases in driving forces have been shown to result in the rapid breakdown of supersaturation, leading to the formation of glassy amorphous aggregates (19). The importance of supersaturation has recently been reported in the context of widespread aggregation and neurodegenerative diseases (24).…”
mentioning
confidence: 99%